2007
DOI: 10.1007/s10396-007-0156-9
|View full text |Cite
|
Sign up to set email alerts
|

Portal gas in a patient with acute obstructive cholangitis: report of a case with emphasis on US findings

Abstract: Portal gas is relatively rare, and its relationship to ischemic bowel diseases has been emphasized. We report the case of a 70-year-old woman with acute obstructive cholangitis in whom portal gas was detected by ultrasonography (US) but not by computed tomography (CT). The former showed multiple echo spots moving in the portal vein. Doppler signals confirmed them to be bidirectional and spiky, which immediately led to the diagnosis of portal gas. Immediate appropriate antibiotic treatment and biliary drainage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…As has been reported in the literature [7,8], US is considered to be more sensitive than CT in the detection of very small amounts of gas. In fact, in our case, gas extending to the liver was easily detected by US, but there were no correlative CT findings.…”
Section: Discussionmentioning
confidence: 90%
“…As has been reported in the literature [7,8], US is considered to be more sensitive than CT in the detection of very small amounts of gas. In fact, in our case, gas extending to the liver was easily detected by US, but there were no correlative CT findings.…”
Section: Discussionmentioning
confidence: 90%
“…Second, it compromises the linearity of the frequency analyzer and displays an artifactual vertical linear waveform (apparently composed of a wide range of frequencies). As has been stressed in the literature, US is considered to be more sensitive than CT for the detection of very small amounts of portal gas, and the final diagnosis of portal gas is now believed be made based on US findings alone [9,31]. Recently, Ijuin et al reported two cases of portal gas in which color Doppler US was useful in the diagnosis.…”
Section: Discussionmentioning
confidence: 93%
“…However, the concept of portal gas changed over time [13,15,19]. As experience with noninvasive medical imaging of the abdomen has accumulated, it has become apparent that it occurs following Crohn's disease [19], ulcerative colitis [19], diverticulitis [17], enteritis [17,20,27], blunt abdominal trauma [15], gastric ulcer [19], intra-abdominal abscess [12,18], lumbar puncture [25], transplant rejection [6,7], and cholangitis [5,[9][10][11]31]. To our knowledge, there are no previous reports of portal gas due to alphaglucosidase inhibitors in the English-language literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations